Analysis of Government Policy in Economic Recovery During Pandemic in Indonesia - Muhlis Madani; Nursaleh Hartaman (Universitas Sultan Ageng Tirtayasa, 2022)
The Covid-19 pandemic affected both the health and economy of different countries, including Indonesia. This led to the issuance of several policies by the government to ensure economic recovery. Therefore, this study aims to examine the government policies implemented as a response to the impact of Covid-19. These policies are generally grouped into four which include fiscal, monetary, macroprudential, and emergency liquidity. A descriptive qualitative method was used to analyze their performance in dealing with the economic crisis caused by Covid-19 using Nvivo12 Plus software. The results showed that the most widely used is the fiscal policy with 62% followed by macroprudential with 20% while monetary and emergency liquidity is 9% and 6%, respectively. This implied that fiscal policy is the main support for the Indonesian government's economic recovery.